Implementasi Model Atik dalam Mengembangkan Kecerdasan Kinestetik di Pos PAUD Sedap Malam 16 - Muhammad Fakhruddin Robbani; Novi Yastuti; Ai Siti Aisah; Nurlina Roslina; Sri Watini (Jurnal Syntax Admiration, 2024)
There are a number of intelligences within children those if developed can become special potentials and talents, one of which is kinesthetic intelligence. One of the efforts to improve kinesthetic intelligence in children can be done with fun activities, one of which is with a well-known early childhood learning model, namely the ATIK model (Observe, Imitate and Do). This study aims to develop an ATIK model in improving children's ability to observe, imitate, and be able to perform movements with the hope and purpose of improving kinesthetic intelligence. The study used descriptive qualitative methods. The data source came from group B students of PAUD Sedap Malam 16 Post Students totaling 15 students. Data collection through observation, interviews and documentation. The results showed that the implementation of the ATIK model was effective in developing children's kinesthetic intelligence through foot pattern motoric play activities. The ATIK model in the game imitating foot patterns provides an increase in children's curiosity by observing, imitating and working so that children's kinesthetic development activities are carried out happily, purposefully and meaningfully.